Applications of puni’s link model to the psychological preparation of a football team before competition - Ureña Bonilla, Pedro (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2005)
The link model proposed by Puni is based on a number of key steps for the psychological preparation of athletes before competition. Reference is made to (a) the selection of necessary, sufficient, and reliable information regarding details of the next competition and the particularities of the opponent; (b) analysis of the team’s own resources and potential; (c) definition of game strategies and specific individual objectives; (d) updating of personally and socially important motivations in accordance with competition objectives; (e) modeling of the circumstances for the next competition; (f) special preparation for the competition using obstacles with different levels of difficulty (particularly unexpected situations); (g) definition of self regulatory mechanisms of unfavorable internal emotional states, and (h) selection and use of techniques to trigger optimal psychophysical states before competition.